MOBILE HEALTH CHECKUP FOR THE OLDER PERSON TO IMPROVE QUALITY OF LIFE: EFFORTS TO IMPLEMENT SDGS GOAL 3 - Fatwa Latifatul Fajriyah (Universitas Airlangga, 2023)
Introduction: Health service programs in an area can help improve the health quality of the older people. The importance of maintaining the quality of life of the older people include optimizing the productivity of the older people, increasing public awareness, and early screening for non-communicable diseases. Mobile inspection is one form of implementing sustainable development goals goal 3 . The purpose of this program is to improve the quality of public health, especially the older people with disabilities as the implementation of goal 3 in the SDGs. Methods: This program is a mobile inspection program which is a follow-up program from the older people Integrated Healthcare Center. The location of the program is in Dadapan Village, Kabat, Banyuwangi. Characteristics of the target older people are the older people who have degenerative diseases with special needs so they cannot visit health facilities. The older people are given free health checks, blood pressure checks, then health counseling is provided, and finally the older people are given PMT for the older people to support their nutritional needs. Results: There were three target older people, then the Village Nurse and the team headed to the target older people home. The examination includes checking the blood pressure of the older people, providing health counseling for natural patients as well as recommendations for healthy living behaviors which include drinking enough water, getting enough sleep, not thinking too much, eating nutritious food in accordance with the recommended diet based on health status. Conclusion: Mobile examinations for the older people are very much needed, but the limited number of health workers in the local area is an obstacle that needs attention. The urgency of the older people mobile examination, among others, is to provide nutrition screening, delay the acceleration of the progression of degenerative diseases, and increase education related to health and nutrition for the older people. Moreover, mobile inspection is a program that is suitable for SDGs goal 3, namely good health and well-being.